Conference Report / AAWM Special Topics Symposium 2023. Theoretical, Analytical, and Cognitive Approaches to Rhythm and Meter in World Musics - Nicely, Tiffany (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2025)
The study of temporality in world musics raises several questions regarding how music is organized and perceived. The proliferation of theories and points of view to arise in the past two decades attests to the importance of and interest in topics related to this field. The Analytical Approaches to World Musics Special Topics Symposium on Theoretical, Analytical, and Cognitive Approaches to Rhythm and Meter in World Musics brought together forty scholars with fresh approaches to this field. This online conference took place over four days in June 2023. Co-chaired by Lina Tabak and the author of this report, the symposium featured six paper sessions, a special session planned by the organizing committee, a panel discussion organized by the program committee, a book dialogue, and a keynote by Daniel Avorgbedor. Presenters affiliated with six continents took part. The symposium was co-sponsored by the Analytical Approaches to World Musics Journal, the CUNY Graduate Center, the Barry S. Brook Center for Music Research and Documentation (CUNY), and the International Foundation for the Theory and Analysis of World Musics (IFTAWM).